Construção filosófica da realidade e suas estruturas epistemologia genética, animismo e artificialismo - Freitas, Sérgio Francisco de (Editora Oficina Universitária, 2022)
This book seeks to discuss aspects of the philosophical (and scientific) construction of reality and its structures, based on works in Genetic Epistemology. In particular, an epistemological analysis of some of the main aspects of the notions of child animism and artificialism is carried out, through the Model of the System of Schemes of Actions and Operations on Symbols and Signs, proposed by Tassinari, and the integration of structures is discussed. that make them possible in the structures necessary for our philosophical (and scientific) knowledge of reality.